The Determinants of Computer Based Information System Performance - Mansour, Ali H.; Watson, Hugh J. (Academy of Management Journal, 1980)
Computer based information system performance can be conceptualized as being a function of computer hardware and software, behavioral, structural, and environmental variables. To explore this conceptual model, data were collected from 108 private and governmental organizations. The data provide useful insights into the determinants of computer based information system performance.